Comparative Review of Stunting Prevalence Rates in Banten Province, Causal Factors and Preventive-Curative Measures - Sugiharto, Adam; Riany, Yulina Eva (Journal of Family Sciences, 2024)
This research is important because it has a novel to stunting intervention through a family approach. The research also answers previous researchers' expectations regarding the scarcity of research on stunting with a family approach. This research is a cross-sectional study conducted in March-May 2023 using secondary data processed from the 2021 Family Data Collection (PK21) data which is then carried out with a descriptive analysis. Banten Province has a number of families at risk of stunting, one-third of the total families in the province. Namely, 2,658,505 families were recorded and 885,301 families at risk of stunting. In sequence the number of families at risk of stunting in regencies and cities in Banten Province from the largest to the smallest is Cilegon City 219,973 families, Serang City 143,187 families, Tangerang City 118,273 families, South Tangerang City 126,800 families, Pandeglang Regency 115,807 families, Lebak Regency 74,313 families, Serang District 52,204 families and Tangerang District 43,744 families. This study concludes that Serang City, South Tangerang City and Pandeglang Regency are 3 districts/cities that have data on families at risk of stunting exceeding families that are not at risk of stunting in these districts/cities. Lebak, Pandeglang and Serang Regencies which border the Indian Ocean have the dominant factor causing stunting from the sanitation aspect. This study concluded that three times the number of family assistance staff from families at risk of stunting is needed in the context of stunting eradication and stunting prevention in the future.